CEO Activism and Corporate Reputation: How Authenticity and CSR Mitigate Stakeholder Misalignment - Li, Lambert Zixin; Soule, Sarah A. (Journal of Management Studies, 2026)
Abstract Previous research suggests that the effect of CEO activism depends on its alignment with stakeholders’ political ideology. We examine when and why CEO activism can enhance corporate reputation across the ideological spectrum. Integrating signalling theory with a cognitive perspective on reputation formation, we argue that the reputational impact of CEO activism depends on the firm’s corporate social responsibility (CSR), which fosters perceptions of organizational authenticity. Using a national survey and an experiment, we find that CEO activism improves corporate reputation through perceived moral authenticity. This effect is stronger when firms hold B Corp certification, engage in philanthropic donations, or are perceived as more socially responsible. Although stakeholders rate firms as more reputable when their political ideology aligns with the CEO’s activism, this relationship weakens when firms engage in CSR, thereby signalling authenticity. These findings demonstrate how non‐market strategies interact to shape corporate reputation and inform corporate sociopolitical advocacy among heterogeneous audiences.